The role of ageing in the wish to be dead: disentangling age, period and cohort effects in suicide ideation in European population. (18th February 2021) - Cabello, M.; Rico-Uribe, L. A.; Martinez-Ávila, J. C.; Sánchez-Niubò, A.; Caballero, F. F.; Borges, G.; Mellor-Marsá, B.; Haro, J. M.; Prina, M.; Koskinen, S.; Ayuso-Mateos, J. L.
Abstract: Aims: To investigate potential age, period and birth cohort effects in the prevalence of suicide ideation in European ageing population. Methods: A total of 50 782 community-dwelling adults (aged + 50) from 20 different European countries were collected in the Survey Health Ageing and Retirement study. A multilevel logistic regression model of repeated measures was modelled to assess the effects of age and other variables, including the variability of observations over three levels: birth cohort groups, time period assessment and individual differences. Results: The larger effect of variability was attributed to individual-level factors (57.8%). Youngest-old people (65–79 years) showed lower suicide ideation than middle-aged people (50–64 years). No significative differences were found for suicide ideation between middle-aged people and oldest-old (80 + years). Only 0.85% and 0.13% of the total variability of suicide ideation accounted for birth cohort and period effects, respectively. Cohorts born between 1941 and 1944 possessed the lowest estimates of suicide ideation. Conversely, suicide ideation started to rise with post-War generations and reached a significant level for people born from 1953–1957 to 1961–1964. Regarding the time period, participants assessed in 2006–2007 showed a lower likelihood of suicide ideation. The rest of the cohorts and period groups did not show any significant effect on the prevalence of suicide ideation. Conclusions: Our results suggest that age and suicide ideation relationship is not linear in middle and older age. The European Baby boomers born from 50s to mid-60s might report higher suicide ideation than their ancestors. This scenario would imply a greater need for mental healthcare services for older people in the future.